Correlation between Clinical Patterns of Poisoning and Forensic Toxicological Findings in Emergency Department Deaths. A Cross-Sectional Clinical Study - Rabia Parveen, Iffat Imtiaz Iffi, Fariha Tariq, Farhat Sultana, Mansoora Mirza, Nomira Waheed (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Poisoning remains a major cause of morbidity and mortality in emergency departments, particularly in low- and middle-income countries. Accurate identification of toxic agents is often hindered by limited clinical information, delayed presentation, and lack of diagnostic facilities. Objectives: This study aimed to evaluate the correlation between clinical patterns of poisoning and forensic toxicological findings in deaths presenting to the emergency department. Methodology: This cross-sectional study was conducted at a tertiary care hospital in Pakistan from July 2022 to July 2023. A total of 49 poisoning-related fatalities underwent complete medico-legal autopsies with detailed toxicological analysis. Demographic data, clinical features, suspected toxins, and emergency interventions were recorded from ED records and autopsy reports. Toxicological testing was performed using thin-layer chromatography, gas chromatography-mass spectrometry, and HPLC. Statistical analysis included descriptive frequencies, Chi-square test, and Cohen’s kappa coefficient. Results: The majority of victims were male (63.3%), with the 21–30-year age group being most affected. The most common toxins identified were organophosphates (30.6%) and pharmaceutical drugs (24.5%). Clinical suspicion matched toxicological findings in only 51% of cases. The agreement between clinical and forensic findings was moderate (Cohen’s κ = 0.44; p < 0.05). Vomiting, unconsciousness, and respiratory distress were the most common presenting symptoms. Antidotes were administered in just 18.4% of cases. Conclusion: There is a significant mismatch between clinically suspected and confirmed toxins in fatal poisoning cases. Routine forensic toxicology, emergency physician training, and access to point-of-care diagnostics are essential to improve early detection, targeted treatment, and mortality outcomes in acute poisoning. Keywords: Poisoning deaths, emergency medicine, forensic toxicology, organophosphates, toxicology mismatch, Cohen’s kappa, Pakistan, clinical–forensic correlation.